Economic evaluation of the Good School Toolkit: an intervention for reducing violence in primary schools in Uganda. Issue 2 (17th April 2018) - Greco, Giulia; Knight, Louise; Ssekadde, Willington; Namy, Sophie; Naker, Dipak; Devries, Karen
Abstract : Introduction: This paper presents the cost and cost-effectiveness of the Good School Toolkit (GST), a programme aimed at reducing physical violence perpetrated by school staff to students in Uganda. Methods: The effectiveness of the Toolkit was tested with a cluster randomised controlled trial in 42 primary schools in Luwero District, Uganda. A full economic costing evaluation and cost-effectiveness analysis were conducted alongside the trial. Both financial and economic costs were collected retrospectively from the provider's perspective to estimate total and unit costs. Results: The total cost of setting up and running the Toolkit over the 18-month trial period is estimated at US397 233, excluding process monitor (M&E) activities. The cost to run the intervention is US7429 per school annually, or US15 per primary school pupil annually, in the trial intervention schools. It is estimated that the intervention has averted 1620 cases of past-week physical violence during the 18-month implementation period. The total cost per case of violence averted is US244, and the annual implementation cost is US96 per case averted during the trial. Conclusions: The GST is a cost-effective intervention for reducing violence against pupils in primary schools in Uganda. It compares favourably against other violence reduction interventions in the region.